Development and Psychometric Properties of the Questionnaire for Assessing Educational Podcasts (QAEP) - Alarcón, Rafael; Blanca, María J. (Frontiers in Psychology, 2020)
The aim of this research was to develop and validate the Questionnaire for Assessing Educational Podcasts (QAEP), an instrument designed to gather students’ views about four dimensions of educational podcasts: access and use, design and structure, content adequacy, and value as an aid to learning. In study 1 we gathered validity evidence based on test content by asking a panel of experts to rate the clarity and relevance of items. Study 2 examined the psychometric properties of the QAEP, including confirmatory factor analysis with cross-validation to test the factor structure of the questionnaire, as well as item and reliability analysis. The results from study 1 showed that the experts considered the items to be clearly worded and relevant in terms of their content. The results from study 2 showed a factor structure consistent with the underlying dimensions, as well as configural and metric invariance across groups. The item analysis and internal consistency for scores on each factor and for total scores were also satisfactory. The scores obtained on the QAEP provide teachers with direct student feedback and highlight those aspects that need to be enhanced in order to improve the teaching/learning process.